Transverse chromatic offsets with pupil displacements in the human eye: sources of variability and methods for real-time correction - Boehm, Alexandra E. (Biomed Opt Express, 2019)
Tracking SLO systems equipped to perform retinally targeted stimulus delivery typically use near-IR wavelengths for retinal imaging and eye tracking and visible wavelengths for stimulation. The lateral offsets between wavelengths caused by transverse chromatic aberration (TCA) must be carefully corrected in order to deliver targeted stimuli to the correct location on the retina. However, both the magnitude and direction of the TCA offset is dependent on the position of the eye’s pupil relative to the incoming beam, and thus can change dynamically within an experimental session without proper control of the pupil position. The goals of this study were twofold: 1) To assess sources of variability in TCA alignments as a function of pupil displacements in an SLO and 2) To demonstrate a novel method for real-time correction of chromatic offsets. To summarize, we found substantial between- and within-subject variability in TCA in the presence of monochromatic aberrations. When adaptive optics was used to fully correct for monochromatic aberrations, variability both within and between observers was minimized. In a second experiment, we demonstrate that pupil tracking can be used to update stimulus delivery in the SLO in real time to correct for variability in chromatic offsets with pupil displacements.